Students’ Self-esteem and Their English Achievement - Sanger, Alan Hubert; Rantung, Fanny; Corte_Real, Cristina Marcal (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
The purpose of this study was to find the level of students' self-esteem and is intended to see the level of students' English achievement. Moreover, this study aimed to find out whether there was any significant correlation between students' self-esteem and their English achievement. This study, which focused on self-esteem and English achievement, might give some practical contributions to the teaching and learning process. It can help English teachers to realize the capability of the students who have high self-esteem and low self-esteem in relation to students' English achievement. About this, English teachers may help, guide, or give motivation to students who have problems with their studies. This research focused on the area of student's self-esteem and English achievement. This study involved the grade XII science one and social one student of SMA Unklab who enrolled in the second semester of the 2015/2016 academic school year. The level of students' English achievement was good, which means that they understand clearly what their teacher taught them in the classroom, and they are interested in learning English. Unfortunately, the result showed that there was no significant correlation between students' self-esteem and their English achievement. It means that students' English achievement was not associated with their self-esteem.